História da equiparação do Colégio Marista Arquidiocesano de São Paulo ao Colégio Pedro II (1900-1940) - Pedro, Ricardo Tomasiello (2014)
The Archdiocesan School was founded in 1858, and it is considered one of the oldest schools of São Paulo city. Due to its strong connection to secondary education, the school tried to equate to Pedro II School. Such an attempt meant, among other things, to guarantee that the school s students had access to higher education without having to apply for new tests or exams. In order to obtain this privilege it was necessary, in the curriculum organization, that the school should be equated to the role model institution in this educational level. Under the Marist Brothers management, the school obtained the definitive equivalence in 1934, during the term of Francisco Campos s Reform (Decree no. 19.890/1931). This dissertation intends to historicize the equivalence process of the Marist Archdiocesan School of São Paulo, under the management of this religious congregation, attempting to understand the construction of such process. The strategies used by a private school were identified a confessional approach to adapt to the educational demands of a secular view in order to verify how the guidelines provided by the Education National Department were followed. For this research, the analysis was primarily of the documents on the equivalence belonging to the National Archives (RJ) and of the case itself available in the Memorial s collection of the Marist Archdiocesan School of São Paulo